(untitled) (Bangladesh Journal of Medical Science, 2022)
Objectives: In pregnant women in developing nations iron deficiency anemia is common. The motherfetus homeostasis may be adversely affected by the demands in pregnancy. This can lead to adverse fetomaternal outcomes like intrauterine growth retardation ,premature delivery, and neonatal and perinatal death. Therefore it is important to understand the relation between maternal and fetal iron handling as this may help in further implementation of measures to prevent iron deficiency in pregnancy and infancy and improve outcomes. Thus, this study was conducted to explore the effect of maternal iron deficiency anemia on newborn iron stores. Methods: The study was conducted in the Department of Obstetrics and Gynecology, Smt. Sucheta Kriplani Hospital, New Delhi, India between November 2014 to March 2016. It was an observational cross sectional study with sample size of 100 antenatal women diagnosed with iron deficiency anemia.We divided the mothers into groups with mild, moderate and severe anemia respectively. The maternal serum ferritin levels were compared with the newborn hemoglobin and serum ferritin levels. Results: Between the three groups the baseline characteristics were comparable. The newborns of mothers with severe anemia had lower Apgar scores and a greater risk of admission. The birth weight did not differ among the groups. The severity of anemia increased with the parity.The cord blood hemoglobin between the groups was comparable, however the cord blood ferritin levels were directly related to maternal hemoglobin values . In those with severe anemia, a positive association was found between maternal ferritin and cord blood hemoglobin and maternal hemoglobin and cord blood serum ferritin. A positive association was also found between maternal hemoglobin and cord blood hemoglobin. Conclusion: The study supports the fact that fetal needs dictate the placental iron demand. With increasing severity of anemia the fetus starts showing decreased serum ferritin and this finally results in iron deficiency at birth. Although the fetal weight and haemoglobin are not compromised with increasing severity of anemia in our study, increased fetal risk manifested by worsening Apgar scores and increased newborn admissions occurred as anemia worsened. This study supports the fact that maternal deficiency of iron affects the newborn iron profile and this reiterates the imperative role of iron supplementation during pregnancy. Bangladesh Journal of Medical Science Vol. 21 No. 03 July’22 Page: 620-625